THE INFLUENCE OF ELSHESKIN INSTAGRAM CONTENT FEATURING A DOWN SYNDROME MODEL ON AUDIENCE PERCEPTION - Anjani R, Hafidha; Cahyani, Reggina; Kharsatul K, Nila; Achyana, M. Arfan (Universitas Mercu Buana, 2025)
The aim of this research is to find out how the public views Elsheskin's Instagram post featuring a model with Down syndrome. Audience perception and cognitive theory are used in this research. The audience that uses the criteria to view Elsheskin's Instagram content is the research population. In this case, the researchers identified a population of Indonesian women aged 17-25 years. There is a quantitative descriptive research design applied. The survey approach used in collecting data for this research was by distributing questionnaires via Google Form media. Elsheskin's Instagram content was viewed by 112 respondents selected using a purposive sampling technique. The findings of this study suggest that when viewers view content about beauty featuring models with Down syndrome, their perceptions are affected. This is demonstrated by increased awareness of the skincare industry, positive perceptions of the Elsheskin brand, and their original content concepts that highlight equality for all women.The aim of this research is to find out how the public views Elsheskin's Instagram post featuring a model with Down syndrome. Audience perception and cognitive theory are used in this research. The audience that uses the criteria to view Elsheskin's Instagram content is the research population. In this case, the researchers identified a population of Indonesian women aged 17-25 years. There is a quantitative descriptive research design applied. The survey approach used in collecting data for this research was by distributing questionnaires via Google Form media. Elsheskin's Instagram content was viewed by 112 respondents selected using a purposive sampling technique. The findings of this study suggest that when viewers view content about beauty featuring models with Down syndrome, their perceptions are affected. This is demonstrated by increased awareness of the skincare industry, positive perceptions of the Elsheskin brand, and their original content concepts that highlight equality for all women.